TAZ inhibits glucocorticoid receptor and coordinates hepatic glucose homeostasis in normal physiological states - Simiao Xu (eLife Sciences Publications Ltd, 2021)
The elucidation of the mechanisms whereby the liver maintains glucose homeostasis is crucial for the understanding of physiological and pathological states. Here, we show a novel role of hepatic transcriptional co-activator with PDZ-binding motif (TAZ) in the inhibition of glucocorticoid receptor (GR). TAZ is abundantly expressed in pericentral hepatocytes and its expression is markedly reduced by fasting. TAZ interacts via its WW domain with the ligand-binding domain of GR to limit the binding of GR to the GR response element in gluconeogenic gene promoters. Therefore, liver-specific TAZ knockout mice show increases in glucose production and blood glucose concentration. Conversely, the overexpression of TAZ in mouse liver reduces the binding of GR to gluconeogenic gene promoters and glucose production. Thus, our findings demonstrate that hepatic TAZ inhibits GR transactivation of gluconeogenic genes and coordinates gluconeogenesis in response to physiological fasting and feeding.